Interlinks of fiscal decentralization and public investment in Pakistan - Imran Hanif; Imran Sharif Chaudhry (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Present work is an attempt to explore intersperse of fiscal decentralization and public investment in Pakistan. The study used a time series data from 1972 to 2013 and Johansen cointegration procedure is used for empirical investigation. It is reported that in the long run, fiscal autonomy to lower tiers of governments may help to improve the tax revenue in one fold and public investment in next fold. More importantly, the addition in subnational revenue and expenditures shares in total government revenue and expenditures will improve the level of public investment and also accelerate the economy towards high economic growth in Pakistan. These findings may also supportive for other developing countries which are struggling to adopt the decentralization process like Pakistan. Finally, the study suggested that a clear mandate of fiscal responsibilities at central and provincial level is also needed to improve the benefits of fiscal decentralization in Pakistan.
Keywords: 330; cointegration; decentralization; expenditures; Pakistan; public investment